National and international financial reporting standard convergence and the relevance for nonparticipants in capital markets: a preparer perspective / Victoria Wise, Jeffrey Faux - Wise, Victoria; Faux, Jeffrey (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
This study presents some implications of recent policy moves to enhance the harmonisation of financial reporting and disclosure by adopting international financial reporting standards. In particular the impact on small organisations that do not participate in capital markets is considered. The results of a survey of practitioners indicate a perception that the non-capital market sector is likely to be significantly affected by the additional reporting burden that convergence with international financial reporting standards imposes. On the whole the results show there was concern that the traditional users of the financial reports of organisations who do not participate in capital markets, would have limited if any, use for financial reports that conformed to international financial reporting standards. The results of this study have implications for nations such as Malaysia and New Zealand, which are currently engaging in the differential reporting debate